Enteroviral and herpes simplex virus central nervous system infections in infants < 90 days old: a Paediatric Investigators’ Collaborative Network on Infections in Canada (PICNIC) study - Petel, Dara; Barton, Michelle; Renaud, Christian; Ouchenir, Lynda; Brophy, Jason; Bowes, Jennifer; Khan, Sarah; Bitnun, Ari; McDonald, Jane; Boisvert, Andrée-Anne; Ting, Joseph; Roberts, Ashley; et al. (Université d'Ottawa | University of Ottawa, 2020)
Abstract Background The relative contribution of viruses to central nervous system (CNS) infections in young infants is not clear. For viral CNS infections, there are limited data on features that suggest HSV etiology or on predictors of unfavorable outcome. Methods In this cross-sectional retrospective study, seven centers from the Pediatric Investigators Collaborative Network on Infections in Canada identified infants < 90 days of age with CNS infection proven to be due to enterovirus (EV) or herpes simplex virus (HSV) January 1, 2013 through December 31, 2014. Results Of 174 CNS infections with a proven etiology, EV accounted for 103 (59%) and HSV for 7 (4%). All HSV cases and 41 (40%) EV cases presented before 21 days of age. Four HSV cases (57%) and 5 EV cases (5%) had seizures. Three (43%) HSV and 23 (23%) EV cases lacked cerebrospinal fluid (CSF) pleocytosis. HSV cases were more likely to require ICU admission (p = 0.010), present with seizures (p = 0.031) and have extra-CNS disease (p < 0.001). Unfavorable outcome occurred in 12 cases (11% of all EV and HSV infections) but was more likely following HSV than EV infection (4 (57%) versus 8 (8%); p = 0.002). Conclusions Viruses accounted for approximately two-thirds of proven CNS infections in the first 90 days of life. Empiric therapy for HSV should be considered in suspected CNS infections in the first 21 days even in the absence of CSF pleocytosis unless CSF parameters are suggestive of bacterial meningitis. Neurodevelopmental follow-up should be considered in infants whose course of illness is complicated by seizures.